PENGARUH ELEUHTERINE PALMIFOLIA (L) MERR TERHADAP PROLIFERASI SEL TUMOR PADA TIKUS SPRAGUE DAWLEY DENGAN KANKER PAYUDARA - Ratna Widayati; Yan Wisnu Prajoko; Udadi Sadhana (Unram Medical Journal, 2022)
Background : Immunotherapy is widely used to increase the response rate of chemotherapy drugs. Eleuhterine palmifolia (L) Merr or dayak onion are known to contain phytochemical compounds that have antiproliferative effects, and have been used as anti-cancer empirical therapies. This study aimed to prove the antiproliferative effect of Eleuhterine palmifolia (L) Merr extract in Sprague-Dawley rats with breast cancer. Methods : This study used 18 Sprague-dawley rats, divided into 3 groups, K, P1 and P2. K was given regular feed, P1 received adriamycin 5 mg/kgBW single dose, P2 received adriamycin 5 mg/kgBW single dose and extract of dayak onion 105 mg/kgBW/day for 3 weeks. Results : Difference in tumor size before and after treatment was 7.2 ± 2.57 mm (K), 3.23 ± 3.03 mm (P1), 3.14 ± 2.65 mm (P2), with p value is 0,157 (p>0,05). Ki-67 index calculations are 11.1 ± 7.27% (K), 9.64 ± 6.99% (P1), 9.58 ± 3.52% (P2), with p value is 0,704 (p>0,05). Conclusion : The addition of Eleuhterine palmifolia (L) Merr (dayak onion) extract did not cause a significant difference in tumor cell proliferation in Sprague-Dawley rats with breast cancer.